Reliability of Squat Kinetics in Well-Trained Rugby Players: Implications for Monitoring Training. Issue 10 (October 2019) - Appleby, Brendyn B.; Cormack, Stuart J.; Newton, Robert U.
Abstract : Abstract: Appleby, BB, Cormack, SJ, and Newton, RU. Reliability of squat kinetics in well-trained rugby players: implications for monitoring training. J Strength Cond Res 33(10): 2635–2640, 2019—The aim of this study was to determine the within-session reliability in kinetic variables of the squat in well-trained athletes during a typical resistance training protocol. Fifteen subjects completed 2 testing sessions. Session 1 was establishment of 1 repetition maximum (1RM) squat, and session 2 involved 2 sets of 2 maximal effort repetitions of the squat at 70, 80, and 90% of 1RM with 3D motion analysis and ground reaction force (GRF) measurement using 2 in-ground triaxial force plates. Reliability was calculated using typical error ± 90% confidence limits, expressed as the coefficient of variation and intraclass correlation coefficient. The smallest worthwhile change (SWC%), calculated as 0.2 × between-subject SD, was used to determine the smallest important change in performance. Peak GRF and average GRF were found to have acceptable measures of reliability with the combined left and right leg average GRF capable of detecting the SWC. Independent limb contributions were reliable (left and right, or dominant and nondominant). Reliable kinetics can be obtained in back squat performance typical of a resistance training session in well-trained athletes. This suggests that coaches integrating force plate technology within training sessions may effectively capture between 1 and 6 training sets among several athletes, facilitating analysis and intervention on larger data sets.